Structure Formation of Binary Blends of Amphiphilic Block Copolymers in Solution and in Bulk. Issue 13 (25th April 2017) - Radjabian, Maryam; Abetz, Clarissa; Fischer, Birgit; Meyer, Andreas; Lademann, Brigitte; Abetz, Volker
Abstract : Solutions of block copolymer blends show mixed microdomains above the critical micelle concentration and show a long period in the bulk, which depends on the number averaged molecular weight with a power law. This scaling behavior differs from the scaling behavior of the surface structure of integral asymmetric membranes made from similar blends. Abstract : The self‐assembly and structure formation in binary blends of asymmetric polystyrene‐ block ‐poly(4‐vinylpyridine) diblock copolymers in different solvent systems and the bulk morphology of the blend films are studied by using dynamic light scattering, small‐angle X‐ray scattering, and transmission electron microscopy. In dilute solutions, the chains of pure diblock copolymers or binary blends of diblock copolymers having similar or different molecular weights remain as unimers, form common micelles in selective solvents or form unimers in coexistence with micelles in slightly selective solvents or solvent mixtures. The blends show mixing of the chemically similar blocks in the blend films and solutions at high concentrations. A single‐phase with common spherical morphology is formed in the blend films similar with the morphology of the individual components in the pure state. The characteristic length scale of the blends depends on the number average molecular weight following the typical scaling behavior of a strongly segregated block copolymer.